2019
DOI: 10.30534/ijatcse/2019/87862019
|View full text |Cite
|
Sign up to set email alerts
|

Fused Random Pooling in Convolutional Neural Network for Herbal Plants Image Classification

Abstract: Convolutional Neural Network (CNN) faces concerns on overfitting. The CNN model learns during the training process but may not be able to classify new data correctly. Hence, the accuracy is higher in the training set than in the validation set. This occurs despite the breakthrough in CNN even if it is considered state of the art in image analysis. In this study, the fused random pooling is presented to create enhanced pooled feature maps, in that way, reducing overfitting and improving classification accuracy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The adoption of ANN as a learning analytic for harmonizing fees between estate surveyors and valuers (S & V) and the clients was successful as some pattern of negotiation fees were obtained. The application of ANN in this context has helped deepened the understanding of this subject matter as similarly applied in [51][52][53][54][55]. It was observed that the peculiarity of the market dynamics over the study area is a vital determinant to estimate or predict harmonized fees.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of ANN as a learning analytic for harmonizing fees between estate surveyors and valuers (S & V) and the clients was successful as some pattern of negotiation fees were obtained. The application of ANN in this context has helped deepened the understanding of this subject matter as similarly applied in [51][52][53][54][55]. It was observed that the peculiarity of the market dynamics over the study area is a vital determinant to estimate or predict harmonized fees.…”
Section: Discussionmentioning
confidence: 99%
“…In other research, herbal plants have been studied by previous researchers with various case studies, such as the classification of herbal plants according to the type of disease identified through the texture, shape and color of herbal plant diseases [11]. Identification of herbal medicinal plant names, scientific names and remedies on leaf objects [12], [13], so that the identification of herbal plants is able to increase the accuracy of herbal plant recognition with CNN well which is able to achieve a recognition rate above 95% near perfect depending on the quality of the object and other approaches [14], [15], because some herbal plants have a surpa level of similarity such as turmeric and ginger, so a good classification technique approach is needed such as CNN and other algorithms [16].…”
Section: Introductionmentioning
confidence: 99%